2015
DOI: 10.1007/s00213-015-3875-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the dopamine/norepinephrine releaser phenmetrazine on cocaine self-administration and cocaine-primed reinstatement in rats

Abstract: Rationale Like other monoamine releasers such as d-amphetamine, chronic treatment with phenmetrazine can attenuate cocaine self-administration in monkeys. Objectives The present studies extended this finding to rodents and to cocaine-primed reinstatement, a putative laboratory animal model of relapse. Methods In Experiment 1, rats self-administered food pellets or injections of 0.19 mg/kg cocaine (i.v.) under a progressive-ratio schedule. When responding was stable, subcutaneous osmotic pumps were implante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 49 publications
4
12
0
Order By: Relevance
“…Rats were then implanted with a subcutaneous osmotic minipump (Model 2001; Alzet; Cupertino, CA) containing phenmetrazine (25 mg/kg/day) 18 hours prior to beginning the self-administration session. This dose was selected based on the findings in a previous study (Czoty et al., 2015) from our group showing similar effects across several doses of phenmetrazine (25 and 50 mg/kg/day, respectively) on other schedules of cocaine self-administration. Therefore we chose to use the lower dose (25 mg/kg/day) used in that study.…”
Section: Methodsmentioning
confidence: 99%
“…Rats were then implanted with a subcutaneous osmotic minipump (Model 2001; Alzet; Cupertino, CA) containing phenmetrazine (25 mg/kg/day) 18 hours prior to beginning the self-administration session. This dose was selected based on the findings in a previous study (Czoty et al., 2015) from our group showing similar effects across several doses of phenmetrazine (25 and 50 mg/kg/day, respectively) on other schedules of cocaine self-administration. Therefore we chose to use the lower dose (25 mg/kg/day) used in that study.…”
Section: Methodsmentioning
confidence: 99%
“…Rigorous pharmacokinetic studies in nonhuman primates have convincingly demonstrated that the behavioral effects of PDM are due to in vivo conversion to its metabolite, PM (Banks et al, 2013b), which has effects on cocaine self-administration similar to d -amphetamine in monkeys and rodents (Negus et al 2009; Banks et al 2011; Banks et al 2013d; Czoty et al, 2015). In the present studies, blood samples were collected during PDM treatment in an effort to determine how PDM and PM concentrations change during long-term treatment with ascending doses of oral PDM, as well as to provide some information relating circulating PM concentrations to the efficacy of PDM to decrease cocaine self-administration.…”
Section: 0 Discussionmentioning
confidence: 99%
“…After oral administration PDM is converted in the liver to phenmetrazine (PM), an amphetamine-like releaser of dopamine and norepinephrine (Rothman et al, 2002; Negus et al, 2009; Banks et al, 2013b). Preclinical studies have demonstrated that the metabolite PM shares discriminative-stimulus effects with cocaine (Negus et al, 2009; Banks et al, 2011) and can decrease cocaine self-administration in rats and monkeys, as well as cocaine-primed reinstatement in rats, at doses that do not alter food-maintained responding (e.g., Negus et al, 2009; Banks et al, 2013d; Czoty et al, 2015). Orderly pharmacokinetics and behavioral effects have been observed over several weeks of repeated administration of the pro-drug PDM (Banks et al, 2013a, b, c), indicating a sustained conversion of PDM to PM.…”
mentioning
confidence: 99%
“…1 H NMR spectra were referenced to an external TMS reference at δ = 0 ppm. 19 F (376 MHz) spectra were recorded on a Bruker DPX400 NMR spectrometer and the external reference was trifluorotoluene set at δ = -64 ppm.…”
Section: Nuclear Magnetic Resonance Spectroscopymentioning
confidence: 99%
“…[11][12][13] Recent studies indicate that phendimetrazine may be a suitable candidate for the treatment of cocaine addiction. [14][15][16][17][18][19] Phendimetrazine has also been suggested as an effective and safer alternative to d-amphetamine as it may simultaneously function as a monoamine uptake inhibitor (via the parent drug) and as a monoamine releaser (via the active metabolite). [14] However in recent years, it has also been observed that NPS manufacturers are also finding new uses for established (and/or withdrawn) medicines since several derivatives of these medicinal products can be found as 'research chemicals' on the NPS market.…”
Section: Introductionmentioning
confidence: 99%